Toleration in Enlightenment Europe - Grell, Ole Peter 1950-; Porter, Roy 1946-2002 (Cambridge University Press, 2000)
The Enlightenment is often seen as the great age of religious and intellectual toleration, and this 1999 volume is a systematic European survey of the theory, practice, and very real limits to toleration in eighteenth-century Europe. A distinguished international team of contributors demonstrate how the publicists of the European Enlightenment developed earlier ideas about toleration, gradually widening the desire for religious toleration into a philosophy of freedom seen as a fundamental attribute and a precondition for a civilized society. Nonetheless Europe never uniformly or comprehensively embraced toleration during the eighteenth century: although religious toleration was central to the Enlightenment project, advances in toleration were often fragile and short-lived